Iridium-catalyzed reductive etherification of α, β-unsaturated ketones and aldehydes with alcohols. Issue 13 (18th March 2022) - Ouyang, Lu; Xia, Yanping; Miao, Rui; Liao, Jianhua; Luo, Renshi
Abstract : A new protocol for the synthesis of allyl ethers in superior yields through a one-pot sequential reductive etherification and alcohol condensation with α, β-unsaturated ketones and aldehydes. Abstract : An iridium complex-catalyzed reductive etherification of α, β-unsaturated ketones and aldehydes with primary alcohols is presented, affording allyl ethers in excellent yields. Deuterated and control experiments showed that this etherification transformation proceeded through a cascade transfer hydrogenation and alcohol condensation process. Moreover, the utility of this protocol is evidenced by the gram-scale performance.